The tax system in Russia as a differentiation factor of the living standard of the population - I. V. Snimshchikova; K. E. Shamray (Вестник Северо-Кавказского федерального университета, 2023)
The purpose of the study is to analyze the impact of the taxation structure in Russia on the differentiation of the living standard of the population. The relevance of this problem lies in the fact that the future development of the country depends on the level and quality of life of citizens. With the help of comparative analysis, the positive and negative effects of proportional and progressive taxation systems are considered. The consequences of the development of the level of poverty and inequality on the socio-economic situation of the country are noted. The dynamics of inflation and wages of employees are reflected. The assessment and views of both domestic and foreign economic scientists on the quality and efficiency of the use of the tax system and the tax rate are presented. Mathematical calculations were carried out, on the basis of which it was proposed to reduce the income tax rate for low-income citizens, the introduction of a selective tax, the development of which contributes to improving the quality of social services provided by the state. The successful foreign experience of introducing a selective tax by the example of Western European countries is presented. The scientific novelty of the research work is that, based on calculations, the possibility of full exemption from income tax of low-income citizens without prejudice to the state budget has been confirmed. The role of the state in building a society based on justice is determined.